Influence Applied Potential on the Formation of Self-Organized ZnO Nanorod Film and Its Photoelectrochemical Response - Samad, Nur Azimah Abd; Lai, Chin Wei; Hamid, Sharifah Bee Abd (Hindawi Publishing Corporation, 2016)
The present paper reports on the facile formation of ZnO nanorod photocatalyst electrodeposited on Zn foil in the production of hydrogen gas via water photoelectrolysis. Based on the results, ZnO nanorod films were successfully grown via electrochemical deposition in an optimum electrolyte set of 0.5 mM zinc chloride and 0.1 M potassium chloride at pH level of 5-6 and electrochemical deposition temperature of around 70°C. The study was also conducted at a very low stirring rate with different applied potentials. Applied potential was one of the crucial aspects in the formation of self-organized ZnO nanorod film via control of the field-assisted dissolution and field-assisted deposition rates during the electrochemical deposition process. Interestingly, low applied potentials of 1 V during electrochemical deposition produced a high aspect ratio and density of self-organized ZnO nanorod distribution on the Zn substrate with an average diameter and length of ~37.9 nm and ~249.5 nm, respectively. Therefore, it exhibited a high photocurrent density that reached 17.8 mA/cm2 under ultraviolet illumination and 12.94 mA/cm2 under visible illumination. This behaviour was attributed to the faster transport of photogenerated electron/hole pairs in the nanorod’s one-dimensional wall surface, which prevented backward reactions and further reduced the number of recombination centres.